1996
DOI: 10.1046/j.1365-2958.1996.5381060.x
|View full text |Cite
|
Sign up to set email alerts
|

TOL plasmid transcription factor XylS binds specifically to the Pm operator sequence

Abstract: XylS, an AraC family transcription factor, positively regulates transcription of Pseudomonas putida TOL plasmid meta operon from the Pm promoter. A tandem of 15 bp homologous direct repeats, separated by 6 bp and overlapping with the -35 hexamer of the promoter, is required for the activation of Pm by XylS in vivo. In this study we have characterized specific binding of XylS to the Pm operator Om. XylS was overexpressed with an epitope tag in its N-terminus. Tagged XylS (N-XylS) was immunopurified and was show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…1). In favor of this proposal is the observation that a tagged XylS-protein immunoadsorbed onto glass beads produced footprints in vitro, which showed protection of the Gs within the above direct repeat at Ϫ48, Ϫ59, Ϫ60, and Ϫ69 (22). This is in agreement with our in vivo results.…”
Section: Discussionsupporting
confidence: 89%
“…1). In favor of this proposal is the observation that a tagged XylS-protein immunoadsorbed onto glass beads produced footprints in vitro, which showed protection of the Gs within the above direct repeat at Ϫ48, Ϫ59, Ϫ60, and Ϫ69 (22). This is in agreement with our in vivo results.…”
Section: Discussionsupporting
confidence: 89%
“…Single point mutations in the binding site revealed that nucleotides located at Ϫ48 to Ϫ45 and at Ϫ58, Ϫ59, Ϫ61, and Ϫ69 are the most critical bases for appropriate XylS-Pm interactions (7)(8)(9). In vitro footprints obtained with a tagged XylS protein immunoadsorbed onto glass beads supported this organization (10). The arrangement of the two motifs is such that the proximal XylS binding site overlaps by 1 bp the RNA polymerase binding site at Ϫ35 (11) (Fig.…”
mentioning
confidence: 77%
“…DNase I footprinting of the XylS interaction on the P m promoter showed a protected region from nucleotides Ϫ78 to Ϫ28 upstream of the transcription start site (102,103). The protein bound along one side of the DNA, covering four helices and thereby making specific contacts in four adjacent major grooves (102). By earlier sitedirected mutagenesis studies, a consensus direct repeat (TGCA-N 6 -GGNTA), which is present twice in the P m promoter between Ϫ35 and Ϫ49 and between Ϫ56 and Ϫ70, had been identified as the binding determinant (70,78,107).…”
Section: Mechanisms Of Activationmentioning
confidence: 99%
“…This can be concluded from crystallographic data for the two AraC members Rob and MarA (114, 210). DNase I footprinting of the XylS interaction on the P m promoter showed a protected region from nucleotides Ϫ78 to Ϫ28 upstream of the transcription start site (102,103). The protein bound along one side of the DNA, covering four helices and thereby making specific contacts in four adjacent major grooves (102).…”
Section: Mechanisms Of Activationmentioning
confidence: 99%
See 1 more Smart Citation